2022
DOI: 10.3390/pediatric14010003
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasonography in Children with Eosinophilic Esophagitis—A Review

Abstract: Endoscopic ultrasonography (EUS) is a diagnostic endoscopy of the upper gastrointestinal tract, during which ultrasound of nearby organs is also performed. It is also possible to perform a fine needle aspiration biopsy. Currently, EUS is performed more frequently in adults. Despite some limitations, this diagnostic method is also more and more often performed in pediatric patients. Eosinophilic esophagitis (EoE) is a chronic inflammatory disease of the esophagus, which also occurs in children, and leads to irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In parallel with its increased utility in conditions such as inflammatory bowel disease, GI ultrasonography, using advanced ultrasound probes, has shown utility in the assessment of flow through segments of the bowel (44) as well as the stomach (eg, in gastroparesis) (45). The use of endoscopic ultrasound may also provide information on esophageal motility in conditions such as eosinophilic esophagitis (46). Compared to MRI, ultrasonography comes with considerable benefits of lower cost and easier storage and use.…”
Section: Less Invasive Investigative Toolsmentioning
confidence: 99%
“…In parallel with its increased utility in conditions such as inflammatory bowel disease, GI ultrasonography, using advanced ultrasound probes, has shown utility in the assessment of flow through segments of the bowel (44) as well as the stomach (eg, in gastroparesis) (45). The use of endoscopic ultrasound may also provide information on esophageal motility in conditions such as eosinophilic esophagitis (46). Compared to MRI, ultrasonography comes with considerable benefits of lower cost and easier storage and use.…”
Section: Less Invasive Investigative Toolsmentioning
confidence: 99%
“…Most significantly, a couple of anecdotal reports have suggested that the resolution of symptoms, endoscopic abnormalities, and esophageal eosinophilia occur prior to the normalization of the EUS observed esophageal wall thickening in EoE 33,34 . A recent review article on the utilization of EUS in EoE has concluded that preliminary data "suggest that EUS and TWT measurement may become an important test in diagnostics, monitoring the effectiveness of therapy, assessing disease progression, and in individualizing the method and duration of EoE treatment in children" 35 .…”
Section: Endoscopic Ultrasound In Eosinophilic Esophagitismentioning
confidence: 99%